Potential Health Risk to Humans Related to Accumulation of Brodifacoum and Bromadiolone in the Wheat Grown on Rodenticide Contaminated Soil - Hromada R.; Miňo I.; Korytár Ľ.; Holotová E.; Ondrašovič M.; Pošiváková T.; Korim P.; Takáč L. (Folia Veterinaria, 2019)
The aim of this study was to determine in a model experiment the potential residues of bromadiolone and brodifacoum in the wheat grown on soil treated with these rodenticides and to compare them with the respective acceptable daily intake (ADI) in order to obtain information lacking in the scientific literature. The study focused on the level of residues of chronic rodenticides Broder G, with the active ingredient brodifacoum, and DERATION G, with the active ingredient bromadiolone, in wheat (Triticum spp.). The preparations were used in the form of granular bait. In the wheat grown on the soil treated with 100 g.m−2 of the preparation BRODER G, the brodifacoum residues ranged from 0.012 to 0.0218 mg.kg−1, while the treatment of soil with 500 g.m−2 resulted in residues ranging between 0.0344 and 0.0436 mg.kg−1. When using the preparation DE-RATION G, bromadiolone residues ranged between 0.012 and 0.018 mg.kg−1 after the treatment of soil with 100 g.m−2 and between 0.030 and 0.0428 mg.kg−1 after the treatment with 500 g.m−2. We observed that the acceptable daily intake was exceeded significantly in all of the cases and the residual levels depended on the rodenticide dose. In the case of brodifacoum, the ADI was exceeded more than 700-fold at a dose of 100 g.m−2 and more than 1400-fold at a dose of 500 g.m−2 of soil. With bromadio-lone, the ADI was exceeded 150-fold at a dose of 100 g.m−2 and more than 350-fold at a dose of 500 g.m−2. This indicates the risk to consumers from such crops.